Employing Parasite Against Cancer: A Lesson From the Canine Tapeworm Echinococcus Granulocus - Guan, Wang; Zhang, Xiaoqin; Wang, Xiao; Lu, Shun; Yin, Jun; Zhang, Jinxin (Frontiers in Pharmacology, 2019)
Cystic echinococcosis (CE), a devastating zoonotic condition caused by the tapeworm Echinococcus granulosus, remain a significant public health problem worldwide. However, after a negative correlation between solid tumor and CE has been incidentally discovered, accumulating evidences have suggested that this parasite may induce anti-cancer effect through activating host immune response and secreting molecules with anti-cancer potential, which may provide some new understanding for immunotherapy. This article will review the evidences supporting the anti-cancer effect of E. granulosus and its underlying mechanisms, and discuss the possible implications in immunotherapy.